2020
DOI: 10.1111/jcpt.13133
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of ancillary drugs in sevoflurane‐related emergence agitation after paediatric adenotonsillectomy: A Bayesian network meta‐analysis

Abstract: What is known and objective The comparative efficacy of ancillary drugs on sevoflurane‐related emergence agitation (EA) in paediatric anaesthesia for adenotonsillectomy remains unclear. The purpose of this Bayesian network meta‐analysis was to investigate the efficacy of ancillary drugs on sevoflurane‐related EA in paediatric anaesthesia for adenotonsillectomy. Methods MEDLINE, Embase, the Cochrane Library and Web of Science databases were electronically searched to identify randomized controlled trials (RCTs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
2
9
1
Order By: Relevance
“…More prospective studies comparing the effects of different dosages of dexmedetomidine on EA are required to establish the optimal dose. Dexmedetomidine used in tonsillectomy, adenoidectomy, ophthalmologic, and orthopedic surgeries lower the EA incidence compared with saline, which is consistent with the findings of Cho et al (43), Jiao et al (46), and Tan et al (42). Tonsillectomy with or without adenoidectomy is commonly associated with throat pain and discomfort, and the EA risk associated with this procedure is up to 55.88% and may involve "a sense of suffocation" because of edema, difficulty in swallowing, and nausea.…”
Section: Discussionsupporting
confidence: 89%
“…More prospective studies comparing the effects of different dosages of dexmedetomidine on EA are required to establish the optimal dose. Dexmedetomidine used in tonsillectomy, adenoidectomy, ophthalmologic, and orthopedic surgeries lower the EA incidence compared with saline, which is consistent with the findings of Cho et al (43), Jiao et al (46), and Tan et al (42). Tonsillectomy with or without adenoidectomy is commonly associated with throat pain and discomfort, and the EA risk associated with this procedure is up to 55.88% and may involve "a sense of suffocation" because of edema, difficulty in swallowing, and nausea.…”
Section: Discussionsupporting
confidence: 89%
“…Although our study found intraoperative use of benzodiazepines is a possible risk factor for adult EA, many studies 23,24 reported benzodiazepine (eg, midazolam) administration reduced pediatric EA. Thus, whether benzodiazepine administration increase or decrease adult EA needs well‐designed randomized controlled studies.…”
Section: Discussioncontrasting
confidence: 63%
“…review and metaanalysis support the superiority of dexm edetomidine over placebo, midazolam, or opioid in significantly decreasing the incidence of ED in pediatrics aft er anesthesia for various types of surgeries [23]. The same evidence was also confirmed in a network analysis of ped iatric anesthesia for adenotonsillectomy operation [24]. In our trial, dexmedetomidine was given as a single IV dose (0.3 μg/kg).…”
Section: Discussionsupporting
confidence: 68%